IMPLEMENTATION OF THE PROTECTION POLICIES FOR INDONESIA MIGRANT WORKERS IN SUKABUMI : A CASE STUDY AT THE SUKABUMI CITY MANPOWER OFFICE - MELANI FITRA RIZKIANTY; DARMO H SUWIRYO; UNIN NIBI SAPUTRA (CV KULTURA DIGITAL MEDIA, 2021)
This study aimed to determine the implementation of protection policies for Indonesian Migrant Workers and to analyze the inhibiting factors faced by the Sukabumi City Manpower Office to protect Indonesian Migrant Workers. This study used descriptive qualitative method with 6 participants. The data collected through observation, interviews, documentation, and literature study. The results indicated that the implementation of protection policies in Sukabumi City has been successfully implemented but it is not optimal. Improved coordination with regional officials can increase the effectiveness of the implementation of policies to protect Indonesian migrant workers. In addition, socialization or roadshows with large quantity related to the protection for Indonesian migrant workers followed by relevant stakeholders can achieve the objectives of socialization. Socialization can be conducted by utilizing Information Technology such as distributing socialization video content through Social Media. In addition, the Manpower Office should propose a particular budget related to the protection of Indonesian Migrant Workers through the Indonesia State Budget (APBN) as well as the Indonesia Provincial Budget (APBD) or by engaging private sector/overseas job training institutions to cooperate.